Living : Red Dot design yearbook 2016/2017 - Zec, Peter, 1956- (Essen : Red Dot, 2016)
"Living" is a must-have for anyone looking to stay on top of the most current trends in the international product design. The volume focuses the fields of living rooms and bedrooms, household, kitchens, tableware and cooking utensils, lighting and lamps, interior design, as well as urban design and public spaces. Additionally, the design team of the year, as well as designer and jury portraits will be presented.
Text in English and German.
Keywords: Industrial design; Interior decoration